2021
DOI: 10.1002/adpr.202100214
|View full text |Cite
|
Sign up to set email alerts
|

Light Management for Enhancing Optical Gain in a Solar‐Pumped Fiber Laser Employing a Solid‐State Luminescent Solar Concentrator

Abstract: The direct conversion of broadband solar radiation into highly coherent laser radiation has attracted scientific and practical interest in recent years. [1] After the first demonstration of a solar-pumped laser (SPL) in 1963, [2] subsequent studies were focused on improving the laser medium and the solar collector design, thereby achieving state-of-the-art high-power SPLs with solar collecting efficiency of up to 32.5 W m À2 (laser output power per unit area of the solar collector optics). [3,4] Such state-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…124 The latter price is based on a 25 mm layer thickness and even though the application was very different (part of a corrosion resistant layer stack for steel bridges 124 ), it is very similar to the 30 mm layers successfully used for LSC-pumped solar lasers. 125 (iv) Solar cells: as described in Section 2 (LSC Simulation Framework), the highest efficiency c-Si solar cells were selected for edge attachment. These 26.7% efficient devices are assumed to be cut into long strips that are 0.3 cm wide, thus a 1 m 2 LSC will require 120 cm 2 (0.012 m 2 ) of solar cells to cover all four edges.…”
Section: Financial Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…124 The latter price is based on a 25 mm layer thickness and even though the application was very different (part of a corrosion resistant layer stack for steel bridges 124 ), it is very similar to the 30 mm layers successfully used for LSC-pumped solar lasers. 125 (iv) Solar cells: as described in Section 2 (LSC Simulation Framework), the highest efficiency c-Si solar cells were selected for edge attachment. These 26.7% efficient devices are assumed to be cut into long strips that are 0.3 cm wide, thus a 1 m 2 LSC will require 120 cm 2 (0.012 m 2 ) of solar cells to cover all four edges.…”
Section: Financial Considerationsmentioning
confidence: 99%
“…124 The latter price is based on a 25 μm layer thickness and even though the application was very different (part of a corrosion resistant layer stack for steel bridges 124 ), it is very similar to the 30 μm layers successfully used for LSC-pumped solar lasers. 125…”
Section: Financial Considerationsmentioning
confidence: 99%
“…The DM/HRM is the same as in the liquid LSC; however, its confinement efficiency is dramatically improved when the top layer of the dielectric multilayer is in contact with air. Although efficient light confinement is expected from total internal reflection (TIR) between the LSC and air [23], previous research has shown that DM/HR is a necessary component, with 40% of all photons confined by TIR, while the remaining 60% are confined by DH/HRM [22].…”
Section: Current Challenges Of the Fully Planer Splmentioning
confidence: 99%
“…We have already demonstrated the tunability of the fluorescence wavelength in preliminary experiments, and laser oscillation was accomplished under 50× sunlight with a primary concentrator [20]. To address the second problem, we then propose the use of solid-state LSCs [21,22]. Fig.…”
Section: Current Challenges Of the Fully Planer Splmentioning
confidence: 99%
“…The film thickness was 80 μm, and the density was adjusted such that the optical density (OD) at a wavelength of 532 nm was 0.6. For details of the dye film, refer to previous studies [21,22].…”
Section: Configuration Of the Solid-state Lscmentioning
confidence: 99%